DEVELOPING A VIDEO TUTORIAL FOR MAKING FRESHWATER CLAM MEATBALLS (Pilsbryoconcha expressa) BASED ON ENTREPRENEURIAL VALUES FOR SENIOR HIGH SCHOOL - Afreni Hamidah; Ervan Johan Wicaksana; Rani Puji Saputri (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2021)
The purpose of this research is develop a video tutorial for making freshwater clam meatballs (P.expressa) based on entrepreneurial values ​​for high school students. This type of research is R&D research that refers to the 4D development model. The results showed that the entrepreneurial values ​​integrated into the video tutorials are innovation and creativity, commitment, confidence, and hard work. The results of the validation of material experts are 85% and media experts are 90%. The test results of the biology study teacher in the material aspect were 87.5%, the video display aspect was 87.5%, and the benefit aspect was 95%. The results of the perception of the display aspect were 87.4%, the content aspect of the tutorial video was 91.4%, and the benefit aspect was 91.7%. Thus, the entrepreneurship-based video tutorial for making freshwater clam meatballs (P.expressa) is deemed feasible to be used as a learning medium for Animalia material, the role of mollucs in life.